(untitled) (Dhaka Shishu (Children) Hospital Journal, 2024)
Background: Neonatal seizure by itself is not a diagnosis but is a manifestation of an underlying disease of central nervous system which may result due to systemic and biochemical abnormalities. Biochemical disturbances are transient and rapidly correctable. This study aims to assess biochemical abnormalities in neonatal seizure. Objective: Aims of the study were to describe biochemical abnormalities in neonatal seizure. Methods: This cross-sectional study has been conducted in the Department of Paediatrics, Bangladesh Shishu Hospital & Institute from January to July 2020. Neonates admitted with history of convulsion or who developed convulsion during hospitalization were included and neonates having congenital malformation of brain, syndromic baby were excluded from this study. Baseline characteristics of neonates including sex, gestational age, weight, head circumference, details of seizure including age at onset, duration, number, and type were recorded. Blood glucose, serum calcium, sodium, potassium, and magnesium level were done immediate after admission before instituting any specific treatment. Informed verbal consent from caregiver was taken before enrolment. Results: Total 60 neonates presenting with seizure were enrolled in the study. About two-third neonates presented with generalized tonic clonic seizure (43/71.7%). Majority (51/85%) of the neonates had seizure within 72 hours, rest of them after 72 hours. Out of 60, 32(53.3%) neonates had biochemical abnormalities of which 28(87.5%) were non-metabolic and 4(12.5%) were primary metabolic seizures. Hypoglycaemia and hypocalcaemia were equally found in primary metabolic seizure. Non-metabolic seizures were associated with perinatal asphyxia, meningitis, sepsis, and intracranial haemorrhage. Hypoglycaemia (67.8%) was commonest abnormality among secondary causes, followed by hyponatremia (21.4%) and hypocalcaemia (10.7%). Among 32 cases, 66.67% hypoglycaemia and 50% hyponatremia were found in perinatal asphyxia cases, which was higher than other cases. Conclusion: This study showed hypoglycaemia was commonest abnormality among biochemical changes in neonatal seizure. Hypoglycaemia and hyponatremia occur with higher frequency in case of perinatal asphyxia. DS (Child) H J 2023; 39(1): 44-48